Pengaruh Social Media Marketing Dan Influencer Marketing Terhadap Keputusan Pembelian Pada Coffeshop Hanyakopi Pamulang Tangerang Selatan - Ricardo Riswan Halawa; Yuyus Kadarusman (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstract - In the current digital era, social media has become an important platform in business marketing strategies, including the culinary industry such as coffee shops. This study aims to analyze the influence of social media marketing and influencer marketing on consumer purchase decisions at Hanyakopi Pamulang Coffee Shop, South Tangerang. Hanyakopi utilizes Instagram as its main marketing medium and collaborates with local influencers to increase brand awareness and attract consumers. The research method used was quantitative with a descriptive approach. The research population consisted of 1,721 Instagram followers of Hanyakopi Pamulang. The sample was determined using the Slovin formula, resulting in 94 respondents selected through purposive sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using SPSS 26. Analysis techniques included validity testing, reliability testing, classical assumption tests, multiple linear regression analysis, hypothesis testing (t-test and F-test), and coefficient of determination. The results showed that social media marketing has a positive and significant effect on purchase decisions with a t-value of 5.121 > t-table 1.987 and significance of 0.000 < 0.05. Influencer marketing also has a positive and significant effect on purchase decisions with a t-value of 5.166 > t-table 1.987 and significance of 0.000 < 0.05. Simultaneously, both variables have a significant effect on purchase decisions with an F-value of 59.000 > F-table 3.10 and significance of 0.000 < 0.05. The coefficient of determination (R²) value of 0.565 indicates that 56.5% of purchase decisions can be explained by social media marketing and influencer marketing, while the remaining 43.5% is influenced by other factors. This study recommends that Hanyakopi continues to improve the quality of social media content and expand collaborations with relevant influencers.